Initial-boundary Value Problem for the Landau-Lifshitz System with Applied Field (Journal of Partial Differential Equations, 2000)
In this paper, the existence and partial regularity of weak solution to the initial-boundary value problem of Landau-Lifshitz equations with applied fields in a 2D bounded domain are obtained by the penalty method.
Keywords: Weak solution; partial regularity; Landau-Lifshitz equations: applied fields